Penerapan Metode Experiential Learning pada Pembelajaran IPAS untuk Meningkatkan Hasil Belajar Siswa Kelas IV SDN 237/VIII Sidorukun - Maidatul Khusna; Megawati Megawati; Puput Wahyu Hidayat (CV. Master Literasi Indonesia, 2026)
This research was conducted on fourth-grade students at SDN 237/VIII Sidorukun based on initial observations that indicated low student learning outcomes and processes in Natural and Social Sciences. Based on the summative evaluation of the Natural Sciences subject in the odd semester of the 2024/2025 academic year, data showed that only 12% of students successfully achieved the Learning Objective Achievement Criteria (KKTP). The purpose of this study was to determine improvements in the Natural Sciences learning process and outcomes through the application of the Experiential Learning method to fourth-grade students at SDN 237/VIII Sidorukun. The research method used was Classroom Action Research (CAR), conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 17 fourth-grade students at SDN 237/VIII Sidorukun, and the study was conducted in the even semester of the 2024/2025 academic year. Data collection in this study used qualitative data in the form of teacher and student observation sheets, as well as quantitative data obtained from: 1) the percentage of the learning process based on teacher and student observation sheets in implementing the Experiential Learning method during the learning process, 2) the percentage of improvement in student learning outcomes obtained from cognitive test questions. The results of the teacher observation sheets in cycle I showed an average of 76.08%, categorized as Good, and in cycle II increased to 89.12%, categorized as Very Good. The results of the student observation sheets in cycle I showed an average of 50%, categorized as Low, and in cycle II increased to 88.23%, categorized as Very Good. Student learning outcomes in cycle I showed 70.58% of students achieving KKTP (completed) scores, and in cycle II increased to 88.23% of students achieving KKTP (completed).